PERSEPSIMASYARAKAT TERHADAP KEBISINGAN PENANGKARAN BURUNG WALET (Collacalia fuciphaga) DI KELURAHAN RIMBA SEKAMPUNG KOTA DUMAI, RIAU - Yusrizal, Deny; Saam, Zulfan; Tarumun, Suardi (Jurnal Kajian Lingkungan, 2013)
The present research was conducted from October 2012 to November 2012 in Sub RimbaSekampung Village Dumai. It seeks to analyze thenoisefrequency caused swiftletbreedinginRimbaSekampungVillage, Dumaiand to analyzethe communityperceptionof thenoisecaused the swiftletbreedingsin the village. The instruments used in the research were asound level meter (SLM) digital camera. The instrument used to measurementsthe communityperception were questionnaire to see the physiological and psychological disturbances.Ttheresultsshowthat the noises in the radius of 30 and 60 meter have exceded the noise threshold;while in a 90 meter radius, the noise have approached the noise threshold value in the urbanresidential area, namely 55 dB.The community perception of the noises caused by the swiftletbreeding in RimbaSekampung Village is bad. Such a perception has raised physiologicaldisturbances like an unconfortable feeling, a headache, an increased blood pressure and ahearing disturbance. In addition, the noise have also raised psychological disturbances lkeemotional disturbances, stress, distraction and rest disturbance.